Imagining a New Society: Public Painting as Politics in Postwar Finland - Ruohonen, Johanna (fi=Turun yliopisto|en=University of Turku|, 2013)
The thesis is the first comprehensive study on Finnish public painting, public artworks generally referred to as murals or monumental paintings. It focuses on the processes of production of public paintings during the post-WWII decades in Finland and the complex relationships between the political sphere and the production of art. The research studies the networks of agents involved in the production of public paintings. Besides the human agents—artists, assistants, commissioners and viewers—also public paintings were and are agents in the processes of production and in their environments. The research questions can be grouped into three overlapping series of questions: First, the research investigates the production public paintings: What kinds of public paintings were realised in postwar Finland—how, where, by whom and for what purposes? Second, it discusses the publicness of these paintings: How were public paintings defined, and what aspects characterised them as “public”? What was their relation to public space, public authorities, and audience? And third, it explores the politics of public paintings: the relationship between Finnish public painting, nationalism, and the memory of war. To answer these questions, extensive archival work has been performed, and over 200 public paintings have been documented around Finland. The research material has been studied in a sociological framework and in the context of the political and economic history of Finland, employing critical theories on public space and public art as well as theories on the building of nationalism, commemoration, memory, and forgetting. An important aim of this research was to open up a new field of study and position public painting within Finnish art history, from which it has been conspicuous by its absence. The research indicates that public painting was a significant genre of art in postwar Finland. The process of creating a national genre of public painting participated in the defining of municipal and state art politics in the country, and paintings functioned as vehicles of carrying out the agenda of the commissioning bodies. In the formation of municipal art policies in Finland in the 1950s, public painting connected to the same tendency of democratising art as the founding of public art museums. Public painting commissions also functioned as an arena of competition and a means of support for the artists. Public paintings were judged and commissioned within the realm of political decision-making, and they suggested the values of the decision-making groups, generally conveyed as the values of the society. The participation of official agents in the production allocated a position of official art to the genre. Through the material of this research, postwar public painting is seen as an agent in a society searching for a new identity. The postwar public painting production participated in the creation of the Finnish welfare society as indications of a humane society. It continued a tradition of public art production that had been built on nationalist and art educational ideologies in the late 19th and early 20th century. Postwar public paintings promoted the new national narrative of unification by creating an image of a homogeneous society with a harmonious communal life. The paintings laid out an image of Finnishness that was modern but rooted in the agrarian past, of a society that was based on hard work and provided for its members a good life. Postwar public painting was art with a mission, and it created an image of a society with a mission.